THE INFLUENCE OF TEACHER’S ATTENTION OF CREED AND MORALS ON THE FORMATION OF STUDENTS GOOD MORALS AT MTS MHAMMADIYAH LIMBUNG - Ulandari, Ulfa; Ruhaya, Besse; Rusmin B, Muhammad; Nuryamin, Nuryamin; Yahdi, Muhammad (Al Asma: Journal of Islamic Education, 2025)
Teachers are an important part of learning activities and play an important role in forming students' noble character by providing direct attention to encourage and motivate students to get used to having noble character. This study aims to determine and analyze the influence of teacher attention to Akidah Akhlak on the formation of students' noble character at MTs Muhammadiyah Limbung. This study uses a quantitative method with an ex post facto approach. Samples were taken from as many as 46 students from a total population of 227 people, with a proportionate stratified random sampling technique. Data collection was carried out through questionnaires, observations, and documentation. The study showed that teacher attention influenced students' noble character formation. This finding shows the importance of teachers in shaping students' character through consistent and meaningful attention. The implications of this study are the need for training and strengthening the role of teachers in aspects of moral development, integration of noble character values ​​in learning activities, and development of madrasah policies that support the formation of students' character holistically.